2018
DOI: 10.1186/s12884-018-1931-x
|View full text |Cite
|
Sign up to set email alerts
|

Births and induced abortions among women of Russian, Somali and Kurdish origin, and the general population in Finland –comparison of self-reported and register data

Abstract: BackgroundSince reproductive health is often considered a highly sensitive topic, underreporting in surveys and under coverage of register data occurs frequently. This may lead to inaccurate information about the reproductive health. This study compares the proportion of women having births and induced abortions among migrant women of Russian, Somali and Kurdish origin in Finland to women in the general Finnish population and examines the agreement between survey- and register-based data.MethodsThe survey data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
0
11
1
Order By: Relevance
“…The main strength of this study is the use of population-based register data, good quality of the data [23, 28] and the ability to separate first- and second-generation migrants. Most previous studies are based on surveys, which suffer from underreporting of abortions [29, 30] and may struggle to include enough immigrant women. Coverage issues might arise with surveys aimed at migrant populations due to language and cultural barriers, particularly with themes considered sensitive like induced abortion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main strength of this study is the use of population-based register data, good quality of the data [23, 28] and the ability to separate first- and second-generation migrants. Most previous studies are based on surveys, which suffer from underreporting of abortions [29, 30] and may struggle to include enough immigrant women. Coverage issues might arise with surveys aimed at migrant populations due to language and cultural barriers, particularly with themes considered sensitive like induced abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier study has shown that survey-based and register-based information on pregnancy history differ somewhat. Under-coverage of births in the register was observed whereas information on previous induced abortions was more accurate in the register [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that the abortion rate among migrant populations is significantly higher than that among the local residents, accounting for the majority of total induced abortions, especially among young and unmarried women [3,4]. In 2014, the number of the floating population (also known as migrants) in China reached 253 million, more than one-sixth of China’s total population [5].…”
Section: Introductionmentioning
confidence: 99%
“…Equal proportion of respondents in each group having visited a medical doctor is a positive finding as it indicates general accessibility of services, apart from the indication that participants of Somali origin reported lower use. Lower use of services by Somali women is, indeed, somewhat surprising in the light of high level of births compared to the general population [ 64 ], but in line with results of their low participation in cervical cancer screening [ 30 ].…”
Section: Discussionmentioning
confidence: 99%